2017
DOI: 10.1007/978-1-4939-7383-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Infection of Ticks with Borrelia burgdorferi Using a Microinjection Method and Their Detection In Vivo Using Quantitative PCR Targeting flaB RNA

Abstract: Borrelia burgdorferi is maintained in nature by a tick-rodent infection cycle where it traverses and colonizes a variety of host and vector tissues. A tick-borne murine model has been developed to study Lyme disease in the laboratory, which has a substantial impact in advancing our knowledge of spirochete infectivity and pathogenesis. Here, we detail a microinjection-based method for rapid and efficient infection of ticks with B. burgdorferi. While laboratory generation of B. burgdorferi-infected nymphs via na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Even though these methods are simpler and cost effective, generation of tick cohorts with equal number of pathogens in each tick is limited. The success of anal pore microinjection system to generate Lyme disease pathogen B. burgdorferi-infected ticks 41 or tick-borne encephalitis virus family Langat virus-infected ticks 42 suggests that this technique can be easily adopted for generating both extracellular or intracellular tick-borne pathogen-infected ticks, respectively. In this study, we report the use of microinjection system to generate obligate intracellular bacterium A. phagocytophilum-infected unfed nymphs in the laboratory condition and showed that these ticks can efficiently transmit this bacterium to the murine host.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these methods are simpler and cost effective, generation of tick cohorts with equal number of pathogens in each tick is limited. The success of anal pore microinjection system to generate Lyme disease pathogen B. burgdorferi-infected ticks 41 or tick-borne encephalitis virus family Langat virus-infected ticks 42 suggests that this technique can be easily adopted for generating both extracellular or intracellular tick-borne pathogen-infected ticks, respectively. In this study, we report the use of microinjection system to generate obligate intracellular bacterium A. phagocytophilum-infected unfed nymphs in the laboratory condition and showed that these ticks can efficiently transmit this bacterium to the murine host.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of ticks that became infected was reported to be 65% after immersion for 45 minutes in a dense culture of B. burgdorferi B31. Ticks can also be infected by microinjection (Kariu et al, 2011;Smith et al, 2018).…”
Section: Approaches For Assessing Potential Vaccine Efficacy In Vitromentioning
confidence: 99%